2020
DOI: 10.1080/00207454.2020.1782905
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of risk factors for the conversion of mild cognitive impairment to dementia

Abstract: Supplementary Table 1. Demographic characteristics of MCI patients with different outcomes in 2011 Variable Total(n=433) MCIp(n=77) MCIs(n=356) t/χ 2 P Age(years) 68.13±7.53 71.60±7.86 67.38±7.25 4.559 <0.001 Number of births 2.00±0.99 2.31±1.21 1.93±0.93 2.618 0.010

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…There were discrepant findings in a 6-year follow-up of 441 community-dwelling persons with MCI, in which depression as measured by the Hamilton depression scale was no more common in those who progressed to dementia than in those with MCI who did not progress so [ 7 ]. That discrepant finding may relate to the population that was studied because a review of 14 published studies showed a 44.3% prevalence of depression in 1899 hospitalized patients with MCI but only 15.7% in 775 community-dwelling patients.…”
Section: Depression and Admentioning
confidence: 99%
“…There were discrepant findings in a 6-year follow-up of 441 community-dwelling persons with MCI, in which depression as measured by the Hamilton depression scale was no more common in those who progressed to dementia than in those with MCI who did not progress so [ 7 ]. That discrepant finding may relate to the population that was studied because a review of 14 published studies showed a 44.3% prevalence of depression in 1899 hospitalized patients with MCI but only 15.7% in 775 community-dwelling patients.…”
Section: Depression and Admentioning
confidence: 99%
“…2 Epidemiological studies indicate that SCD may represent a predementia stage of Alzheimer disease (AD), 3,4 with an increased risk of conver-sion to MCI and dementia, thus being considered a risk factor for objective cognitive disorders. 5 A meta-analysis has suggested that the annual progression rates of SCD to MCI and dementia are 7% and 2%, respectively. 4 A recent meta-analysis 6 found that the mean prevalence of SCD in communitybased studies was 46% and confirmed that patients with SCD have an increased risk of developing MCI and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…The strongest risk factors of MCI included old age and having a specific form of a gene known as APOE e4, which is also linked to Alzheimer's disease [ 7 9 ]. Epidemiological studies have also identified other medical conditions and lifestyles as risk factors for MCI, including high blood pressure, diabetes mellitus, depression, low education level, less frequent participation in stimulating activities mentally or socially, smoking, low vegetable and high saturated fat consumption [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%